Income inequality in Malaysia: a decomposition analysis by income sources - A. Hakim, Roslan (Universiti Utara Malaysia, 2000)
This paper examines the contribution of inequality in income sources to total inequality in Malaysia using the Malaysian Family Life Survey (MFLS) data. Two measures of inequality are calculated - the Shorrock's and Gini indices of inequality. Both inequality indices are decomposed to its various income sources contribution to total inequality. The results show that a large portion of the total inequality in Malaysia was attributable to labour income, i.e. paid and self-employment. The contribution of capital and transfer incomes (i.e. rent, interest and dividends as well as pensions and EPF) to total inequality appeared to be relatively small. Nonetheless, its contribution has increased. The large contribution of paid and self-employment to total inequality was not because these sources were the most unequally distributed sources, but rather due to their importance in total household income. The results also show that income from rent, interest and dividends was found to have a consistently unequalising effect on inequality. The decomposition analysis highlighted the importance of reducing inequality in paid employment, self-employment, as well as rent, interest and dividends as the best strategy to reduce income inequality in Malaysia.